Protective Effects of Pleurotus tuber-regium on Carbon- Tetrachloride Induced Testicular Injury in Sprague Dawley Rats - Okolo, Kenneth O.; Siminialayi, Iyeopu M.; Orisakwe, Orish E. (Frontiers in Pharmacology, 2016)
The high rate of male infertility and the meargre resources to manage same in sub Saharan Africa have necessitated the search for cost effective and available alternatives. Mushrooms have been used traditionally in folk medicine and as nutraceuticals. This study has investigated the effect of the wild mushroom Pleurotus tuber-regium on carbon tetrachloride (CCl4) deleterious effects on the reproductive system of male rats. Thirty six rats were divided into six groups of six animals each. Group I (negative control) received 10ml/kg olive oil intraperitoneal weekly in addition to feed and water ad libitum. Group II (positive control) received CCl4 10ml/kg (30% in Olive oil) weekly. Group III, IV and V received 100mg, 200mg and 500mg P.tuber-regium (33.3% in feed) daily in addition to 10ml/kg CCl4 weekly. Group VI received 500mg P.tuber-regium (33.3% in feed) daily. After four weeks, sperm motility, epididymal count and vitality were determined. Serum malondialdehyde MDA, testosterone, Luteinizing hormone L H, Follicle stimulating hormone FSH, prolactin and oestradiol were estimated using enzyme-linked immunosorbent assay (ELISA) kits. Histopathologic examinations of the testis were carried out. Carbon tetrachloride significantly reduced the sperm motility (54.33 ± 3.79 %), epididymal count (28.73 ± 2.86 × 106 /ml, vitality(4.96 ± 0.62), LH (0.88 ± 0.14), FSH (2.04 ± 0.33) and Testosterone (2.02 ± 0.24) when compared with control(89.33 ± 9.01), 91.91 ± 1.92 × 106 /ml, 13.12 ± 0.19, 2.74 ± 0.32, 3.64 ± 0.62 and 4.16 ± 0.23 respectively which were reversed by P. tuber-regium administration. Co-administration of P.tuber-regium plus CCl4 significantly reduced malondialdehyde MDA level. Pleurotus tuber-regium showed dose dependent ameliorative activity against CCl4 deleterious action on the testis and may be beneficial in the management of male infertility.